Atmospheric organophosphate esters in the Western Antarctic Peninsula over 2014–2018: Occurrence, temporal trend and source implication. (December 2020) - Wang, Chu; Wang, Pu; Zhao, Junpeng; Fu, Min; Zhang, Lin; Li, Yingming; Yang, Ruiqiang; Zhu, Ying; Fu, Jianjie; Zhang, Qinghua; Jiang, Guibin
Abstract: Organophosphate esters (OPEs) were comprehensively investigated in the air samples collected using high-volume samplers near the Chinese Great Wall Station in the Western Antarctic Peninsula over the period of 2014–2018. The concentrations of ∑8 OPEs (gaseous + particle phases) ranged from 33.9 to 404 pg/m 3 with a geometric mean of 119 ± 12.0 pg/m 3 . Tris [(2R)-1-chloro-2-propyl] phosphate (TCIPP) and tris(2-chloroethyl) phosphate (TCEP) dominated in the gaseous phase, while tris-n-butyl phosphate (TnBP) was the most abundant OPEs in the particle phase, followed by TCIPP and TCEP. An apparently temporal trend was observed for atmospheric ∑8 OPEs over the five years, with a doubling time of about 3.8 years, which indicated continuous inputs of OPEs into the sampling area. The particle-bound ∑8 OPEs accounted for 45% of the total, generally lower than that reported in the Arctic. Gas-particle partitioning modeling suggested that the partitioning of OPEs with higher log K OA values approached the steady state in the Antarctic air. The back-trajectory modeling showed that high levels of OPEs were usually associated with air inputs from the northwest of the peninsula. This suggested that long-range transport from South America, which was confirmed by the no temperature dependencies of OPEs concentrations (excluding TnBP). Nevertheless, a steady high level of particle-bound TnBP implied local sources in the Western Antarctic Peninsula, which required further investigation in future works. Graphical abstract: Image 1 Highlights: Atmospheric OPEs were investigated in the Western Antarctic from 2014 to 2018. Increasing trends were found for TCIPP and TCEP in the Western Antarctic air. OPEs were generally associated with air inputs from the northwest of the peninsula. A steady high level of particle-bound TnBP implied occurrence of local sources. Abstract : Capsule: 1. Increasing temporal trends were found for TCIPP and TCEP in the Western Antarctic Peninsula atmosphere from 2014 to 2018. 2. Atmospheric OPEs were generally associated with air inputs from the northwest of the peninsula.